Treatment-associated Fatigue in Cancer Patients Treated with Immune Checkpoint Inhibitors; a Systematic Review and Meta-analysis. Issue 10 (October 2016) - Abdel-Rahman, O.; Helbling, D.; Schmidt, J.; Petrausch, U.; Giryes, A.; Mehrabi, A.; Schöb, O.; Mannhart, M.; Zidan, A.; Oweira, H.
Abstract: Aims: Fatigue is one of the most prominent side-effects of immune checkpoint inhibition. Therefore, we assessed the risk of fatigue associated with inhibitors of the immune checkpoints. Materials and methods: We examined data from the Medline and Google Scholar databases. We also examined original studies and review articles for cross-references. Eligible studies included randomised phase II and phase III trials of patients with cancer treated with ipilimumab, nivolumab, pembrolizumab and tremelimumab. The authors extracted relevant information on participants ' characteristics, all-grade and high-grade fatigue and information on the methodology of the studies. Results: In total, 17 trials were considered eligible for the meta-analysis. The odds ratio for all-grade fatigue for CTLA-4 inhibitors was 1.23 (95% confidence interval 1.07, 1.41; P  = 0.003) and for high-grade fatigue was 1.72 (95% confidence interval 1.26, 2.33; P  = 0.0005). Moreover, the odds ratio for all-grade fatigue for PD-1 inhibitors was 0.72 (95% confidence interval 0.62, 0.84; P  < 0.0001) and for high-grade fatigue was 0.36 (95% confidence interval 0.23, 0.56; P  < 0.00001). Conclusions: The analysis of data showed that CTLA-4 inhibitors seem to be associated with a higher risk of all- and high-grade fatigue compared with control regimens, whereas PD-1 inhibitors seem to be associated with a lower risk of all- and high-grade fatigue compared with control regimens. Highlights: Fatigue is one of the most prominent side-effects of immune checkpoint inhibition. CTLA-4 inhibitors are associated with a higher risk of fatigue compared with controls. PD-1 inhibitors are associated with a lower risk of fatigue compared with controls.